Japanese encephalitis vaccination in HIV-infected children with immune recovery after highly active antiretroviral therapy - Thanyawee Puthanakit (2018)
HIV-infected children are vulnerable to infections by vaccine preventable pathogens. However, they have poorer responses to childhood immunization than healthy children. The objectives of this study are to determine the prevalence of Japanese encephalitis (JE) protective antibody in HIV-infected children with immune recovery after highly active antiretroviral therapy (HAART) and evaluate response to JE revaccination. JE neutralizing antibody titer of plasma was determined by a plaque reduction neutralization assay. An antibody titer of more than 1:10 was defined as protective antibody. Children who did not have protective antibody to JE were enrolled to receive a two-dose JE revaccination during the study. There were 96 children with mean age of 9.7 years (S.D. 2.6) and mean CD4 percentage of 25 (S.D. 5) who participated in the study. Forty-four children (46%) had protective antibody to JE. A two-dose JE revaccination was administered to 50 children who did not have JE antibody. At 1 month after revaccination, 44 children (88%) developed protective antibody. This study demonstrated that there is a low prevalence of JE protective antibody in HIV-infected children despite history of JE primary childhood vaccination. However, the majority of HIV-infected children with immune recovery after HAART can develop protective antibody after JE revaccination. © 2007 Elsevier Ltd. All rights reserved.